La escuela como organización que mejora - Simón Rodriguez; Carolina Salinas (Recherches en Éducation)
This paper develops conceptual guidelines about learning and school improvement. For this, we conducted a search and review national and international literature. From this review, we understand the continuity and sustainability of an improvement when applied deepen knowledge in the various programs (internal and external to schools), and in which the practices of principals, teachers and students do not understand how the addition or substitution of other new. The paper develops the key concepts of school autonomy, organizational learning, improvement and sustainability of distributed leadership, culminating in a proposal that accounts for the interaction of these concepts as variables that allow schools to understand how they learn and improve.